ANALISIS KINERJA PUSAT-PUSAT PERTANGGUNGJAWABAN PADA PT. BALI REKA MAHESA CARGO DI DENPASAR - Anak Agung Ngurah Gede Suindrawan; I Nyoman Wirayudi Sanjaya (Forum Manajemen, 2012)
In an effort to assess the companyâ€™s ï¬ nancial performance namely liabilitycenters those are cost centers, revenue centers, proï¬ t centers and investment centers.The ï¬ nancial assessment is done by comparing the budget with a good realization ofrevenues, cost, and proï¬ t before taxes or by using ï¬ nancial ratios without correlatingthe income earned by the investments that are used to generate the proï¬ ts as wellas the sales volume achieved by the company. The Appraisals of performance have not been able to indicate efï¬ cient cost, how much earned income without having to pay attention the cost, how much the ability to generate proï¬ ts when compared withthe sales volume and how much the ability to generate proï¬ ts when compared withthe asset being used. How was the accountability centers performance observedbased on the cost centers, revenue centers, proï¬ t centers and investment centers atPT. Reka Mahesa Cargo Bali in Denpasar from 2008 to 2010, which is analyzedby quantitative analysis; furthermore, analysis is used in this research consistedof: cost centers analysis, revenue centers analysis, proï¬ t centers analysis includeGross Proï¬ t Margin, Operating Proï¬ t Margin and Net Proï¬ t Margin, as well asinvestment center analysis that is Return on Investment, Residual Income and Returnon Equity. Based on the study and discussion result obtained the conclusion that thecost centers performance at PT. Reka Mahesa Cargo Bali in Denpasar from 2008to 2010 is not efï¬ cient. Revenue centers performance from 2008 to 2010 showed afavorable outcome. The results of the proï¬ t centers analysis based on Gross Proï¬ tMargin, Operating Proï¬ t Margin and Net Proï¬ t Margin is known the performanceof PT. Reka Mahesa Cargo Bali in Denpasar from 2008 to 2010 showed a favorableoutcome. The results of the center investment analysis based on the Return onInvestment, Residual Income, and Return on Equity is known the performance ofPT. Reka Mahesa Cargo Bali in Denpasar from 2008 to 2010 showed a favorableoutcome. It is recommended to control the business cost in an effort to improve theefï¬ ciency in which economic resources can be used effectively, so that there is nowaste of costs; as a result, the proï¬ ts obtained would be more optimal.